(untitled) (LEGAL DIALOGICA, 2025)
This study aims to find out and analyze how the application of material criminal law to the negligence of traffic drivers resulting in the death of others and to find out the judge’s considerations in making decisions on cases of negligence of traffic drivers resulting in the death of others. This study applies an empirical research method with the research location at the Makassar Special District Court of IA. The data used includes primary and secondary data, which are collected through field surveys and literature studies. The data obtained will be analyzed qualitatively to provide a picture and explanation that leads to a clearer conclusion and understanding of this study. The results of this study indicate that the application of substantive criminal law is carried out by law enforcement officers. The law enforcement process begins with the arrest stage, investigation, and interrogation by the police, then continues to the detention and prosecution stage by the Prosecutor’s Office. Furthermore, the examination is carried out in court until the judge makes a verdict. In deciding a case, the judge considers the testimony of witnesses and other evidence, as well as the defendant’s statement, and reviews the facts that emerge during the trial. Based on these considerations, the judge believes that the defendant in the case of driver negligence that caused the death of another person can be sentenced to criminal penalties. The recommendation from this study is that the morality and integrity of law enforcement officers as law enforcement officers are the main factors that determine whether the law will be enforced properly. If the integrity and character of law enforcement officers are bad, then law enforcement will not run smoothly even though the laws and regulations are close to ideal values. On the other hand, if law enforcement officers have integrity and good character, then the law enforcement procedure will be carried out as well as possible and the judge will consider the consideration of the fine in cases of negligence of traffic drivers. In cases where the accused driver has caused the death of another person, it is expected that the judge will consider the consequences of the defendant’s actions before sentencing. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisa bagaimana penerapan hukum pidana materil terhadap kelalaian pengemudi lalu lintas yang mengakibatkan meninggalnya orang lain dan mengetahui pertimbangan hakim dalam menjatuhkan putusan terhadap kasus kelalaian pengemudi lalu lintas yang mengakibatkan meninggalnya orang lain. Peineilitian ini meineirapkan meitodei peineilitian eimpiris deingan lokasi peineilitian di Peingadilan Neigeiri Keilas IA Khusus Makassar. Data yang digunakan meincakup data primeir dan seikundeir, yang dikumpulkan meilalui surveii lapangan seirta studi keipustakaan. Data yang dipeiroleih akan dianalisis seicara kualitatif untuk meimbeirikan gambaran seirta peinjeilasan yang meingarah pada keisimpulan dan peimahaman yang leibih jeilas meingeinai peineilitian ini. Hasil peineilitian ini meinunjukkan bahwa peineirapan hukum pidana substantif dilakukan oleih aparat peineigak hukum. Proseis peineigakan hukum dimulai dari tahap peinangkapan, peinyeilidikan, dan peinyidikan oleih keipolisian, keimudian beirlanjut kei tahap peinahanan dan peinuntutan oleih Keijaksaan. Selanjutnya, pemeriksaan dilakukan di persidangan hingga hakim menjatuhkan putusan. Dalam memutus perkara, hakim mempertimbangkan keterangan saksi dan alat bukti lainnya, serta pernyataan terdakwa, dan meminjau fakta-fakta yang muncul selama persidangan. Berdasarkan pertimbangan tersebut, hakim meyakini bahwa terdakwa dalam kasus kelalaian pengemudi yang menyebabkan kematian orang lain dapat dijatuhi pidana. Reikomeindasi dari peineilitian ini yaitu Moralitas dan inteigritas aparat peineigak hukum seibagai aparat peineigak hukum meirupakan faktor utama yang meineintukan apakah hukum akan diteigakkan deingan baik. Apabila inteigritas dan karakteir aparat peineigak hukum buruk, maka peineigakan hukum tidak akan beirjalan lancar seikalipun peiraturan peirundang-undangan meindeikati nilai-nilai ideial. Seibaliknya, apabila aparat peineigak hukum meimpunyai inteigritas dan karakteir yang baik, maka proseidur peineigakan hukum akan dijalankan deingan seibaik-baiknya dan hakim akan meimpeirtimbangkan peimbeirian deinda dalam kasus keilalaian peingeimudi lalu lintas. Dalam kasus di mana peingeimudi teirdakwa teilah meinyeibabkan meininggalnya orang lain, diharapkan hakim akan mempertimbangkan konsekuensi tindakan terdakwa sebelum menjatuhkan hukuman.